2007
DOI: 10.1002/ajim.20429
|View full text |Cite
|
Sign up to set email alerts
|

The association of socioeconomic status and psychosocial and physical workplace factors with musculoskeletal injury in hospital workers

Abstract: In this study, the risk of WRMSDs was more strongly influenced by specific psychosocial and physical job-related exposures than by broad socioeconomic factors such as education and income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 103 publications
7
68
1
1
Order By: Relevance
“…The present results corroborate earlier findings of these associations 10,25) . Additionally and importantly, current findings show that high effort and high rewards of effort-reward associations calls for attention.…”
Section: Effort-reward Imbalancesupporting
confidence: 93%
See 2 more Smart Citations
“…The present results corroborate earlier findings of these associations 10,25) . Additionally and importantly, current findings show that high effort and high rewards of effort-reward associations calls for attention.…”
Section: Effort-reward Imbalancesupporting
confidence: 93%
“…A review of 63 selected studies with regard to WMSD risk factors indicated that heavy physical work, smoking, being overweight, high psychosocial work demands and the existence of co-morbidities were common factors associated with WMSDs 8) . Regarding psychosocial factors, some studies have used theory-based job stress measures [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] such as the JCD model 26) and the ERI model 27) . The JCD model predicts that the-adverse health effects occur when job demands are high and decision latitude is low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgel et al (18) found that ERI was associated cross-sectionally with severe shoulder pain in hotel room cleaners. Gillen et al (19) found that it was associated with a risk of neck and upper-extremity injury claims in a case-control study among hospital workers in �an Francisco, U�A. Rugulies & Krause (20) reported that ERI predicted compensated low-back and neck injuries in a 7.5-year prospective study of urban transit operators in �an Francisco.…”
Section: Effort-reward Imbalance Modelmentioning
confidence: 99%
“…Some studies have investigated the relationship of these stressors with health condition, 12,15 mental health, 4 coronary disease, 12,17 and symptoms, signs or disability arising from musculoskeletal problems. 9,10,22 In recent years special attention has been paid to nurses' health. These providers are usually subject to different physical loads determined by psychosocial stressors such as close attention, lack of understanding of the tasks, fast task performance, repetitive and fragmented tasks, low social support, lack of recognition and reward, high emotional demands, night work and lack of job security.…”
Section: Introductionmentioning
confidence: 99%